(untitled) (Philological Studies, 2020)
Nostalgia is the keyword of Vladan Dobrivojević’s novelistic opus—nostalgia for the “original condition”, as B. Hamvas described the primordial, yet highest order of human existence, nostalgia for the God-man, which is exactly what makes it eschatological— and in our intent to describe its nature, we have chosen Where Angels Come From: The Eastern Genealogy (2019), a book modest in volume, which enables us to speak about the central problems of this markedly coherent opus by following the principle of synecdoche. Where Angels Come From is a collection of ten stories which form a nested narrative in The Waterpainter’s Dream (1994–1997), the writer’s encyclopedically conceived trilogy, and it contains the key ideas of The Waterpainter’s Dream, as well as other qualities paradigmatic of the writer’s opus. Taking as our basis an interpretation that links nostalgia to an ideal instead of the past, which would be typical for an 18th-century poem, we show that nostalgic idealization is a characteristic of Dobrivojević’s novels, whose protagonists are led by a longing for an authentic existence. Nostalgia for that which doesn’t exist, and yet it should (a standard of clear, permanent and unquestionable aesthetical and ethical, i.e. evangelical values) is the basic motivation behind his protagonists’ spiritual journey as they come to understand the heavenly origin of the human race, accomplish Christ-like feats and achieve the fullness of their cosmic status. That is why the narrative of return in Dobrivojević’s prose is also connected to the motive of the collective, lost home of the human race. Eschatological nostalgia—the protagonist’s central experience in Where Angels Come From—is primarily defined by a way of life devoted to their theanthropic purpose, which was given to human beings in the very beginning. Its solemn linguistic stylization and the poetics of icon painting explain the liturgical character of this novel in which ontotheological questions are evident.